(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
One of the prioritized activities of commercial banks is formation of loan portfolio. The quality of the loan portfolio of Kazakh commercial banks declined due to the global economic crisis. The main reason for the prolonged financial crisis in Kazakhstan has become risky behavior of banks. The special nature of mediation of commercial banks requires them to balanced approach in the organization of their assets. The article deals with the formation of the loan portfolio of Kazakh and Czech commercial banks, the branch structure of loans and their quality. It was noted that the quality of the loan portfolio depends on the professional conduct of bank employees.